Examining the link between nonmedical use of sedatives, tranquilizers, and pain relievers with dispositions toward impulsivity among college students. (June 2017) - Blanchard, Brittany E.; Stevens, Angela K.; Littlefield, Andrew K.; Talley, Amelia E.; Brown, Jennifer L.
Abstract: Background: The association between impulsive dispositions and the use of the central nervous system (CNS) depressant alcohol has been examined extensively; however, the links between other depressant use (sedatives, tranquilizers, and pain relievers) and impulsivity have been less studied, and findings have been equivocal. This may be due, in part, to varying operationalizations of "impulsivity, " as well as issues related to the lumping versus splitting of various depressant substances when assessing use. The effect of gender on the impulsivity-depressant use relation has also yielded mixed results and remains understudied. The current study sought to determine whether lumping versus splitting of depressant substances and distinct impulsivity-related dispositions, as well as participant gender, impact the depressant-impulsivity relation. Method: Participants were 778 undergraduate students (72% female, 80% White, 23% Hispanic), who completed a battery of self-report assessments online, including the UPPS-P. Results: Hierarchical linear models indicated that specific impulsive dispositions differentiated between users and non-users of specific depressant substances, and these relations varied by gender. For example, sensation seeking significantly differentiated between users and non-users of pain relievers for females only, whereas sensation seeking differentiated between users and non-users of tranquilizers among males but not females. Conclusions: In addition to informing substance use research practices by providing evidence that lumping of depressant substances leads to loss of vital information, as well as demonstrating nuanced gender differences, findings can also inform screening and personality-targeted treatment practices. Highlights: Impulsive trait-nonmedical depressant use relations vary by depressant type. Dispositions toward impulsivity differentially relate to depressant use by gender. Lumping of depressant substances should be avoided in future research.